Pengembangan Media Pembelajaran Puzzle Kata Untuk Meningkatkan Kemampuan Menyusun Kalimat Sederhana Pada Siswa Kelas Iii Sdn 179 Tanah Beru Kec. Bonto Bahari Kab. Bulukumba - Azwa Alif Alisa; Aliem Bahri; Anin Asnidar (Journal on Education, 2024)
This research aims to describe the development of word puzzle learning media in Indonesian language subjects with the aim of improving the ability to compose simple sentences in class III students at SDN 179 Tanah Beru District. Bonto Bahari District. Bulukumba. This research is a type of Research and Development research using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subjects of this research consisted of 46 class III students at SDN 179 Tanah Beru District. Bonto Bahari District. Bulukumba was divided into 2 groups, namely the experimental group and the control group. Data collection techniques in this research used interviews, observation, questionnaires and tests. In this research, the data was processed using quantitative, qualitative analysis techniques and the T-Test. The design of this research is an experimental pre-test and post-test control group design. The media product validation results meet the very valid criteria with a score obtained from the material validator of 88 and a media design validator of 92. This media consists of interesting supporting components and is very easy to use and understand by students, so it gets a positive response from students with results The practicality value of 91.13 is included in the very attractive criteria. In the t-test at a significance level of 0.05, the results obtained were tcount = 6,279 > ttable = 2,015. This shows that there is an increase in students' understanding in the experimental group before and after the implementation of word puzzle media in understanding simple sentence material compared to students in the control group. Based on the results obtained, H0 is rejected and Ha is accepted, so it can be concluded that the use of word puzzle learning media is effective in improving the ability to compose simple sentences in class III students at SDN 179 Tanah Beru District. Bonto Bahari District. Bulukumba.